LANGUAGE AND THE MEDIA: DISCOURSES ABOUT THE ENGLISH LANGUAGE IN BRAZILIAN MEDIA (Polifonia, 2009)
This paper analyses the ways contemporaneous Brazilian media influence the production and circulation of discourses about English, examining how the English language is represented in media discourse. I shall explore how certain ideologies are established by means of a hegemonic discourse about the need that everyone in Brazil should know English, and how this prevalent meaning produces an imaginary effect of inclusion of all Brazilians. However, this discourse is contradicted by covert meanings that English should remain the possession of only a segment of the population.Este artigo analisa a influência da mídia brasileira contemporânea na produção e circulação de discursos sobre a língua inglesa, a partir da observação sobre como o Inglês é representado nesse discurso. A análise explora como certas ideologias são estabelecidas por meio de um dizer hegemônico sobre a necessidade que todos no Brasil teriam de saber inglês e como esse dizer produz um efeito imaginário de inclusão de todos os brasileiros. Todavia, esse dizer é contradito por sentidos velados de que a língua deveria permanecer conhecida por apenas uma parcela da população.